2010
DOI: 10.3233/jad-2010-091315
|View full text |Cite
|
Sign up to set email alerts
|

Is Caffeine a Cognitive Enhancer?

Abstract: Abstract. The effects of caffeine on cognition were reviewed based on the large body of literature available on the topic. Caffeine does not usually affect performance in learning and memory tasks, although caffeine may occasionally have facilitatory or inhibitory effects on memory and learning. Caffeine facilitates learning in tasks in which information is presented passively; in tasks in which material is learned intentionally, caffeine has no effect. Caffeine facilitates performance in tasks involving worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
252
4
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(305 citation statements)
references
References 84 publications
(100 reference statements)
17
252
4
12
Order By: Relevance
“…Moreover, caffeine has been reported to improve concentration (7), attention, psychomotor performance (7,8), and can help sustain attention during demanding tasks (7), with such changes being augmented as a result of exercise (8,9). In light of this, a recent review identified that there was a dearth of data reporting the effects of caffeine on exercise in older adults and this topic merited further scrutiny due to the reported performance enhancing effects in younger populations (4).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, caffeine has been reported to improve concentration (7), attention, psychomotor performance (7,8), and can help sustain attention during demanding tasks (7), with such changes being augmented as a result of exercise (8,9). In light of this, a recent review identified that there was a dearth of data reporting the effects of caffeine on exercise in older adults and this topic merited further scrutiny due to the reported performance enhancing effects in younger populations (4).…”
Section: Introductionmentioning
confidence: 99%
“…This results in the side effects of caffeine outweighing the benefits that consumers seek [20]. While it is indeed true that caffeine boosts moods, alertness and long-term memory, it is advisable to consume recommended proportions of caffeine [20].…”
Section: Introductionmentioning
confidence: 99%
“…While individuals respond differently to stimulants, research has found that caffeine has both positive and negative effects on the body, such as anxiety, insomnia, tachycardia, irritability, Broncho-pulmonary dysplasia and muscle tremors [5,8,16,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…These results add support to prior claims that caffeine ingestion may enhance performance where cognitive and/or perceptual-motor skills are important. 24,25 To some extent the positive impact of caffeine ingestion on such performance is not unexpected. Caffeine ingestion has measureable performance-enhancing abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Such a suggestion is congruent with prior work, suggesting more effective attentional focusing is one of the main mechanisms by which caffeine enhances cognitive and perceptual performance. 2,24 The increased attentional capacity resulting from ingestion of a CNS activator may therefore enable more focused allocation of resources to a given task than without caffeine.…”
Section: Discussionmentioning
confidence: 99%